Pengaruh Retail Activation Aura Kasih Terhadap Brand Image Sampoerna Kayoe pada Instagram @sampoernakayoe - Sharon Astrid Valentina Imanuella Linanto; Mohamad Alppy Valdez (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
Social media is a platform used for sharing information, providing reactions, conducting business, and interacting. Instagram is one of the popular social media platforms used by companies to interact and share information. Sampoerna Kayoe uses Instagram as a tool to change the brand image from its previous name, Samko Timber, through a retail activation strategy in collaboration with Aura Kasih. This study aims to determine whether there is an influence of Aura Kasih's retail activation on the brand image of Sampoerna Kayoe on Instagram @sampoernakayoe, and how significant that influence is. The research uses a quantitative approach with a data sample of 100 respondents who follow Sampoerna Kayoe’s Instagram account. The obtained data was subjected to a normality test to determine whether it was normally distributed, a Pearson Product Moment correlation test to examine the relationship between variables, a coefficient of determination test to measure the magnitude of influence between variables, and a simple linear regression test to assess the strength of the influence exerted. The tests conducted will be analyzed using the SPSS application. The analysis results indicate a moderate positive influence of Aura Kasih's retail activation on the brand image of Sampoerna Kayoe, with a correlation value of 0.484. The results of this study are expected to serve as an evaluation material for Sampoerna Kayoe regarding the performance of the Retail Activation with Aura Kasih, so that more effective campaigns can be carried out in the future.